Truth, Deliberative Democracy, and the Virtues of Accuracy: Is Fake News Destroying the Public Sphere?. (February 2021) - Chambers, Simone
Do fake news and what some have labeled our post-truth predicament represent a new and deadly challenge to the epistemic presuppositions of the public sphere? While many commentators have invoked Hannah Arendt to help answer this question, I argue that Arendt is the wrong place to look. Instead, I suggest that, on one hand, deliberative democracy and Jürgen Habermas' idea of democracy as truth-tracking offer a more helpful framework for assessing and combating the threat of fake news and, on the other hand, Bernard Williams' virtues of accuracy identify the citizen virtues necessary to counteract fake news. The virtues of accuracy, I contend, can be facilitated and encouraged through structural and regulatory features in the public sphere. We are indeed seeing a recalibration and significant push back on fake news due to both structural changes and ordinary citizens becoming more epistemically responsible consumers of digital information.